Analysis of Banking Risks According to IFRS 7 and its Impacts of Financial Failure Forecasting in Iraqi Private Banks - Ghdhaib, Mohanad (International Journal of Indonesian Business Review, 2024)
Understanding the relationship between financial risks and the likelihood of financial failure is crucial for both practitioners and academics. A proper comprehension of these issues helps the banking sector avoid the consequences of failure and enhances risk management practices. The purpose of the current paper is to determine the impact of financial risk analysis according to IFRS 7 in predicting financial failure. A sample of six well-established Iraqi banks was selected, and their financial statements were analyzed for the period from 2019 to 2023. Using a quantitative approach, financial risks were measured through a set of appropriate financial ratios and methods. Financial failure was assessed using the Sherrod model. The results indicated that the financial risks associated with the operations of Iraqi banks ranged from moderate to high, and that risk management practices varied significantly between banks. The findings revealed that the surveyed banks fell within the zone of non-failure indicators. Additionally, the results showed a positive impact of the three types of risks in contributing to financial failure within the sector's banks.